2018
DOI: 10.32504/hspj.v2i3.44
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat pengetahuan penanggulangan bencana dan kesiapsiagaan bencana gempa bumi pada kepala keluarga di Dusun Kiringan Canden Jetis Bantul Yogyakarta

Abstract: Head of Family knowledge about earthquake disaster management is very important in disaster preparedness, it is expected that the community is ready to handle earthquake disaster. In order not to panic and grow negatively against them. The people of Kiringan village are very affected by the earthquake disaster due to disaster prone areas. The purpose of this research is to know the relationship of knowledge level of disaster management with earthquake disaster preparedness to family head in Kiringan Village, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The level of knowledge on disaster management is a basic aspect that should be possessed by every community, including teenagers, to be able to provide information to their family members when a disaster occurs (Setyaningrum & Rumagutawan, 2018). Twigg (2007) states that if individual knowledge including adolescents about hazards, vulnerabilities, risks and risk reduction activities is sufficient, it will be able to create effective community action independently or in collaboration with other stakeholders in dealing with disaster.…”
Section: Resultsmentioning
confidence: 99%
“…The level of knowledge on disaster management is a basic aspect that should be possessed by every community, including teenagers, to be able to provide information to their family members when a disaster occurs (Setyaningrum & Rumagutawan, 2018). Twigg (2007) states that if individual knowledge including adolescents about hazards, vulnerabilities, risks and risk reduction activities is sufficient, it will be able to create effective community action independently or in collaboration with other stakeholders in dealing with disaster.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of disaster preparedness is essential to reduce the risk posed by disasters (Syaifudin, 2018). Knowledge of preparedness is essential for the head of the family to have as a leader in household life and is responsible for conveying information to his family members, and making decisions to act based on the essential truth, the truth that will benefit all members of the household (Setyaningrum, 2018). showed that the majority had a positive attitude with a percentage of 98.6%.…”
Section: Resultsmentioning
confidence: 99%
“…Tingkat pengetahuan penanggulangan bencana akan menjadi aspek dasar yang seyogianya dimiliki oleh semua masyarakat. Pengetahuan tentang penanggulangan bencana ini bermanfaat bagi masyarakat untuk berbagi informasi kepada kerabat atau tetangga apabila suatu saat terjadinya bencana (N. Setyaningrum & Rumagutawan, 2018).…”
Section: Pembahasanunclassified